PENGARUH PERCEIVED SERVICE QUALITY, CITRA MEREK, HARGA, DAN LOKASI TERHADAP KEPUASAN PELANGGAN RESTORAN SOLARIA DI KOTA PONTIANAK - admin, NURUL UTAMININGSIH B11109061 (Jurnal Manajemen Update, 2016)
The research was purposed to find out the influence of perceived service quality, brand-imaged, price and location on satisfaction of Solaria Restaurant’s consumers in Pontianak. This research was taken through survey. The population were Solaria Restaurant’s consumer. The samp;ing were 100 respondent. The sampling technique was purposive sampling. Worker, non-worker with pocket money, and three-times minimal visitor during a year were the criteria of this sampling. The result of this research has shown that perceived service quality was significantly influenced on the satisfaction of Solaria Restaurant’s consumer in Pontianak. Brand-imaged was significantly influenced on satisfaction of Solaria Restaurant’s consumer in Pontianak. Price was significantly influenced on satisfaction of Solaria Restaurant;s consumer in Pontianak. On the other hand, location was not significantly influenced on satisfaction of Solaria Restaurant’s consumer in Pontianak. Keywords (keywords).Perceived Service Quality, Brand, Price, Location and Customer Satisfaction.